Pelaksanaan Hukuman Mati di Indonesia Berdasarkan Aspek Kemanusiaan, Etika, dan Moralitas: Perspektif Keadilan Utilitarian - Ishwara, Ade Sathya Sanathana; Rodliyah, Rodliyah; Pancaningrum, Rina Khairani (CV. Social Politic Genius (SIGn), 2025)
The implementation of capital punishment stipulated in Law Number 2/PNPS/1964 is clearly contrary to the second principle of Pancasila, the noble values enshrined in the 1945 Constitution, and the mandates of international conventions, thereby causing a legal antinomy or conflict of norms. This study employs normative legal research methods to identify legal rules, principles, and doctrines that address the legal issues encountered while utilising a legislative, conceptual, and comparative approach. Research results show the implementation of capital punishment policy should not be solely for the purpose of retribution but should also be based on humanitarian considerations, as stated in the second principle of Pancasila. For example, lethal injection is often considered more humane than other methods of execution. From a utilitarian perspective, this method is acceptable if it provides maximum benefit to society by reducing the suffering of the perpetrator (convicted person). Capital punishment by lethal injection, which has been used in several countries, including China, Thailand, and Vietnam, is considered more humane and upholds ethical and moral values, so lethal injection can be considered as an option for the method of capital punishment in Indonesia to replace the method of execution by firing squad.